Impact of the caFFR-Guided Functional SYNTAX Score on Ventricular Tachycardia/Fibrillation Development in Patients With Acute Myocardial Infarction - Pan, Jiazhi; Zhang, Qiuxia; Lei, Li; Chen, Yaode; Li, Guodong; Liang, Hongbin; Lu, Junyan; Zhang, Xinlu; Tang, Yongzhen; Pu, Jun; Yang, Yining; Mo, Dapeng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: To explore the relationship between the severity of coronary artery disease (CAD) and the occurrence of ventricular tachycardia/ventricular fibrillation (VT/VF) in acute myocardial infarction (AMI) patients. Methods: We retrospectively enrolled 705 AMI patients hospitalized and underwent percutaneous coronary intervention (PCI) in Nanfang Hospital from July 2017 to July 2020. Logistic regression analysis and backward stepwise approach were taken to select the correlation factors. And the receiver operating characteristic curves (ROC) analysis were plotted to observe the discriminative power of SYNTAX score/caFFR guided functional SYNTAX score (SS/FSScaFFR) on the incident VT/VF. Results: 58 (8.2%) patients experienced life-threatening VT/VF. FSScaFFR (OR: 1.155; 95%CI: 1.047 to 1.273; p=0.004) was an independent predictor of VT/VF after AMI. ROC analysis showed that the discriminative power of FSScaFFR on the incident VT/VF was significantly better than SS (0.759 vs. 0.695, p<0.0001). Patients with VT/VF were categorized into 2 groups according to the interval between the onset of AMI and the VT/VF. And the logistic regression analysis revealed that FSScaFFR was a significant independent correlation of early- and late-VT/VF. Conclusion: The incident VT / VF in AMI patients is closely associated with the severity of CAD evaluated by SS and FSScaFFR. Compared to SS, FSScaFFR has a higher correlation with VT/VF. And FSScaFFR was demonstrated to be an independent correlation factor of incident VT/VF after AMI.